Strategy for Internalizing the Value off Character Education Based on Aswaja in Elementary School - Hamidaturrohmah Hamidaturrohmah; Aan Widiyono; Murniati Murniati; Ramadan Basher Imhemd (Program Studi PGMI UIN Salatiga, 2022)
The problem of attitudes and moral decadence of learners is increasingly widespread, making it important to optimize character education from an early age. This research aims to describe the strategy of planting Aswaja-based character values in students in elementary school in order to become a strong foundation. The research method used is descriptive qualitative with a case study. This research was conducted at the Integrated Primary School (SD) Jepara. Collecting data entailed methods of observation, interviews, and documentation. The results of the study show that the strategy of internalizing character values based on Aswaja can be carried out by schools with application in micro contexts and macro contexts. First, the micro context includes: integration with each subject, planting tasamuh, tawazun, ta’adul and tawasuth through habituation of attitudes in daily life, habituation of amaliah Aswaja such as Barzanji activities, Qur'an recitations, grave pilgrimages, and tahlil. Second, the macro context refers to collaboration between schools, parents, and the community. Cooperation with parents lies in the synergy of attitude application at school and at home and doing reflections together; cooperation with the community is carried out through a partnership program to support the quality and character of educational output.